Adaptive backstepping stabilization of nonlinear uncertain systems with quantized input signal - Zhou, Jing (2014)
In this paper, we study a general class of strict feedback nonlinear systems, where the input signal takes quantized values. We consider a stabilization problem for nonlinear uncertain systems via adaptive backstepping approach. The control design is achieved by introducing a hysteretic quantizer to avoid chattering and using backstepping technique. A guideline is derived to select the parameters of the quantizer. The designed controller together with the quantizer ensures the stability of the closed loop system in the sense of signal boundedness. Keywords: Adaptive control, backstepping, quantized control, nonlinear systems, hysteretic quantizer